Perceived Employability, Academic Commitment, and Competency of University Students During the COVID-19 Pandemic: An Exploratory Study of Student Well-Being - Capone, Vincenza; Marino, Leda; Park, Miriam Sang-Ah (Frontiers in Psychology, 2021)
COVID-19 outbreak has led to closure of schools and universities, which forced students to reorganize their daily and academic lives and impacted on their well-being in various ways. The present study aimed to investigate the relationship between students’ perceived employability, self-efficacy, ambition, organizational commitment and career planning, mental and academic well-being and student’s academic burnout, in COVID times. 269 Italian university students participated in an online questionnaire. Our results highlight that students experienced much uncertainty about their employability and career planning. On the other hand, they reported healthy levels of mental and academic well-being, high career ambitions and strong self-efficacy, despite the fear to COVID-19. We suggest that intervention and supportive programs should be offered to students over the long term in order to minimize the negative impact of the pandemic.